Publicity as a Policy Instrument: Analyzing Communication Strategies and Public Perception of Aceh's Teacher Capacity Enhancement Policy - Muryali Muryali; Ahmad Yani; Aiyub Aiyub; Nazaruddin Nazaruddin; Maryam Maryam (SAINTIS Publishing, 2025)
This article examines the application of the principle of publicity in the education policy of the Aceh Provincial Government, with a particular focus on the teacher quality improvement program in rural areas. The principle of publicity refers to openness and transparency in the dissemination of policy information to the public, serving as a critical element in promoting participation and accountability. This study aims to evaluate the extent to which policy communication and publication processes are conducted transparently, and how these processes influence public understanding and engagement. Employing a qualitative approach, data were collected through policy document analysis, content review of online and print media, and in-depth interviews with key stakeholders, including education department officials, school principals, teachers, and representatives of civil society. The findings reveal that publicity plays a strategic role in shaping public perception of education policies, particularly in enhancing the legitimacy and trust of the community toward teacher capacity-building programs. However, the study also identifies a major challenge: limited access to information in rural areas due to inadequate digital infrastructure. This digital divide hinders equitable access to policy information and restricts meaningful public participation in the policy process. These findings underscore the necessity of developing communication strategies that go beyond digital media, incorporating local approaches such as community forums, local radio broadcasts, and engagement with community leaders. In doing so, the principle of publicity can be implemented more inclusively and effectively to support equitable and transformative education development in Aceh Province.